2023
DOI: 10.1128/spectrum.00631-23
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR Interference-Based Inhibition of MAB_0055c Expression Alters Drug Sensitivity in Mycobacterium abscessus

Abstract: In this study, we utilized CRISPR interference (CRISPRi) to specifically target the MAB_0055c gene in M. abscessus , a bacterium that causes difficult-to-treat infections. The study found that silencing the gene lead to increased rifabutin and rifalazil susceptibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Additionally, factors such as aging, underlying pulmonary conditions like cystic fibrosis (CF), and immunocompromised states such as acquired immunodeficiency syndrome (AIDS) contribute to the heightened risk of MAC and M. abscessus infections in numerous regions worldwide (Johansen et al, 2020). M. abscessus infections pose a significant challenge, especially due to their high resistance levels (Nguyen et al, 2024). The clinical manifestations of M. abscessus infection are typically classified as either pulmonary or extrapulmonary disease.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, factors such as aging, underlying pulmonary conditions like cystic fibrosis (CF), and immunocompromised states such as acquired immunodeficiency syndrome (AIDS) contribute to the heightened risk of MAC and M. abscessus infections in numerous regions worldwide (Johansen et al, 2020). M. abscessus infections pose a significant challenge, especially due to their high resistance levels (Nguyen et al, 2024). The clinical manifestations of M. abscessus infection are typically classified as either pulmonary or extrapulmonary disease.…”
Section: Introductionmentioning
confidence: 99%
“…Despite being less harmful to humans when compared to M. tuberculosis , the bacterium responsible for causing tuberculosis, treating lung infections caused by M. abscessus is extremely challenging. This is primarily due to the bacterium’s high resistance to commonly used antibiotics, such as β-lactams, tetracyclines, aminoglycosides, and macrolides (Luthra et al, 2018; Nguyen et al, 2024). Additionally, even anti-tuberculosis drugs like rifampicin and isoniazid prove to be ineffective against M. abscessus .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Springer et al observed that excision of the integrated plasmid is by the integrase and occurs more frequently than anticipated, but can be avoided by utilizing a second nonreplicating Int-containing plasmid Furthermore, integrase-mediated excision of the L5 integrated plasmid can lead to plasmid loss in cases where the integrated plasmid is disadvantageous for the growth of the recombinant strain (195), indicating that the pLJR965 plasmid may be toxic for Mab over a longer period of time. Nevertheless, any loss of the integrated plasmid was not reported when applying the Sth CRISPRi-system on either Msm, Mtb or Mab (146,148,196,197), yet Bosch et al described the use of a suicide plasmid to express Int in order to enhance the stability of the L5 integration during long-term studies (191). It is unclear whether excision of the integrated plasmid occurs more frequently in Mab than in Msm or Mtb, we waited too long in between experiments leading to the loss of the unstable plasmid over time, or if we were unable to correctly translate the Sth CRISPRi-system for use in…”
Section: Iv5 Discussionmentioning
confidence: 99%